PEMBERDAYAAN PEMUDA SEBAGAI GURU SEKOLAH MINGGU DALAM RANGKA MENINGKATKAN PERTUMBUHAN IMAN ANAK - SABATINI, TIYA; JUNTAK , JUSTIN NIAGA SIMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Youth have a very strategic role in national life, including in the religious context. In the environment of Gereja Kristen Jawa (GKJ) Sambirejo, the role of youth is crucial in supporting and continuing the church's mission, including Sunday school activities. Sunday school is an effective means of instilling faith and moral values in children from an early age. Therefore, empowering youth as Sunday school teachers is highly relevant and urgent. In reality, many youths are unwilling to take part in this ministry, despite the church's training and development efforts. This study uses a qualitative descriptive method to examine the youth empowerment process. The research questions for the study titled